PENGARUH TINGKAT KECANDUAN PONSEL TERHADAP EMOSI NEGATIF DENGAN MASALAH INTERPERSONAL SEBAGAI PEMEDIASI PADA APARATUR SIPIL NEGARA PEMKO BANDA ACEH - Nadia Fadhilla; Fairuzzabadi Fairuzzabadi (Departemen Manajemen, 2022)
This study aims to measure the effect of Mobile Phone Addiction Levels to Negative Emotions with Interpersonal Problems as a mediating variable in the Pemko of Banda Aceh City. The sample used in this study were employees of Pemko Banda Aceh City is totaling 297 respondents. Data collection equipment used in this study was a questionnaire. The sampling technique used is stratified random sampling method. Causal Step was used as a method of analysis to determine the effect of all the variables involved. Based on the results of the Causal Step analysis indicated that Mobile Phone Addiction Levels positively influence Negative Emotions, Mobile Phone Addiction Levels influence Interpersonal Problems, Interpersonal Problems positively influence Negative Emotions and Interpersonal Problems partial mediate the relationship between Mobile Phone Addiction Levels and Negative Emotions.